2016
DOI: 10.1007/s10608-016-9798-5
|View full text |Cite
|
Sign up to set email alerts
|

Dampening, Positive Rumination, and Positive Life Events: Associations with Depressive Symptoms in Children at Risk for Depression

Abstract: Blunted positive affect is characteristic of depression. Altered positive affect regulation may contribute to this blunting, and two regulation strategies, dampening positive affect and positive rumination, have been implicated in depression. However, the conditions under which these strategies impart risk/protective effects prior to onset of depression are unknown. The current study examined 81 healthy children (age 7–10) at low and high risk for depression on the basis of maternal history of depression and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 44 publications
0
19
4
Order By: Relevance
“…Low enhancing has indeed been found to predict relative increases in anhedonia-related symptoms, whereas it was not found to predict general depressive symptoms in the same sample (Nelis et al, 2015). In children and early adolescents, again, more dampening related to more concurrent anhedonia, even when controlling for non-anhedonia depressive symptoms (Gilbert et al, 2017).…”
Section: Anhedoniamentioning
confidence: 91%
See 3 more Smart Citations
“…Low enhancing has indeed been found to predict relative increases in anhedonia-related symptoms, whereas it was not found to predict general depressive symptoms in the same sample (Nelis et al, 2015). In children and early adolescents, again, more dampening related to more concurrent anhedonia, even when controlling for non-anhedonia depressive symptoms (Gilbert et al, 2017).…”
Section: Anhedoniamentioning
confidence: 91%
“…Specifically, the association was either not found (Burke, McArthur, Daryanani, Abramson, & Alloy, 2018;Verstraeten, Vasey, Raes, & Bijttebier, 2012), or sometimes only held for a subtype of enhancing (e.g., Dempsey, Gooding, & Jones, 2011;Raes, Daems, Feldman, Johnson, & Van Gucht, 2009). In another study, increased enhancing has been found to be related to higher concurrent depressive symptoms in children at risk for depression (Gilbert, Luking, Pagliaccio, Luby, & Barch, 2017).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Consistent with affect valuation theory (Tsai, 2007), parents may promote different emotions (e.g., calm vs. excited) depending on their emotional goals for their child (Gentzler, Palmer, Yi, Root, & Moran, 2018). Finally, although some research has examined PA regulation in conjunction with NA regulation (e.g., Gilbert, Luking, Pagliaccio, Luby, & Barch, 2016;Graf, Ramsey, Patrick, & Gentzler, 2016;Mancini, Luebbe, & Bell, 2016), none of the quartet papers did. This approach is essential if parents have generally supportive or unsupportive reactions to children's emotions, in which case the association between socialization of savoring and positive child outcomes could be an artifact of this general parenting approach to both positive and negative emotions.…”
Section: Expanding Measurement Tools For Pa and Its Regulationmentioning
confidence: 99%